2003
DOI: 10.1046/j.1471-6712.2003.00118.x
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent subjective well-being and family dynamics

Abstract: The purpose of this study was to examine the relationships between adolescent subjective well-being (SWB) and family dynamics perceived by adolescents and their parents. A sample of 239 pupils (51% female) from seventh and ninth grades completed the Berne questionnaire of SWB (youth form), two subscales from an original Finnish SWB scale and the Family Dynamics Measure II, and one of their parents (n = 239) filled in the Family Dynamics Measure II. Results indicated that parents assessed family dynamics better… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 34 publications
2
18
0
2
Order By: Relevance
“…Most studies have assessed mother-child and father-child relationships as independent variables (Ackard et al 2006;Avison and McAlpine 1992;Meadows et al 2006) or collapsed to give a dichotomous overall parental or family measure (Compan et al 2002;Rask et al 2003) with results often showing gender differences in well-being for boys and girls, as well as differences in the impact of mother-child and father-child relationships. Although most studies have considered supportive relationships/effective parenting as protective factors, The Association Between Adolescent Life Satisfaction 289 or combative relationships/inadequate parental monitoring as risk factors, few studies have considered the impact of both simultaneously.…”
Section: Research Aims and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies have assessed mother-child and father-child relationships as independent variables (Ackard et al 2006;Avison and McAlpine 1992;Meadows et al 2006) or collapsed to give a dichotomous overall parental or family measure (Compan et al 2002;Rask et al 2003) with results often showing gender differences in well-being for boys and girls, as well as differences in the impact of mother-child and father-child relationships. Although most studies have considered supportive relationships/effective parenting as protective factors, The Association Between Adolescent Life Satisfaction 289 or combative relationships/inadequate parental monitoring as risk factors, few studies have considered the impact of both simultaneously.…”
Section: Research Aims and Hypothesesmentioning
confidence: 99%
“…These have found that during adolescence, life satisfaction is strongly influenced by life experiences and relationships, particularly within the context of the family (Edwards and Lopez 2006;Gohm et al 1998;Rask et al 2003). While the use of life satisfaction in young people is in its infancy, other measures of young people's mental well-being are yet to be established for international use (Herman et al 2005).…”
mentioning
confidence: 99%
“…Adolescents' subjective well-being is also related with psychological factors such as internal locus of control and self esteem (Huebner 1991), positive transitions during early adolescence from primary to junior high school (Wigfield et al 1991), peer relations (Hartup and Stevens 1997), personality traits of extraversion and neuroticism and lack of stressful life events (Mcknight et al 2002), somatic diseases (Vargus-Adams 2006;Varni et al 2004), family structure and relationships (Huebner 2004;Huebner et al 2000;Joronen and Kurki 2005;Park 2004;Rask et al 2003;Shek 1998;Shek and Lee 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Bickham et al (1) stated that family members can facilitate positive mental health outcomes, but some adolescents may not want family members involved in their mental health treatment and Rask et al (17) argue that there exists a gap between adolescent and parental perception of family functioning. According to Tossavainen et al (18), active cooperation and parental involvement in health promotional actions is crucial for the results of health promotion activities in school.…”
Section: Discussionmentioning
confidence: 99%